(untitled) (Olhar de Professor, 2023)
The article discusses the repercussions of neoliberal policies on teacher training courses at commodification private Higher Education Institutions (HEIs) in the State of São Paulo. From the lenses of the historical-dialectical method, considering the totality in which Higher Education is inserted and its determinations, it brings discussions derived from theoretical-empirical studies, which occurred in the scope of two doctoral researches (KASSIS, 2021; SALCES, 2020) that, supported by the formulations of Saviani, Pimenta, Libâneo and others, highlight the indispensability of Pedagogy as an epistemological field in initial formation. Based on interviews with students, professors, and coordinators of the undergraduate programs of these HEIs, it became evident that the economicist view of education impacts on the pedagogical, curricular, and management orientations. It defends the urgency of policies that distance themselves from private interests and that drive to the construction of socially fair public school referenced by an emancipatory pedagogy.